"Experience from Rural Electrification in Uganda: A Case Study of a Husk Powered System in Tiribogo Village'' - Okure, Mackay A. E.; Musinguzi, Wilson; Wabwire, Andrew; Bagenda, Ssengonzi (In 9th Sida Reg. Conf, 2014)
To address the need for electricity in some rural communities in Uganda with seasonal agricultural waste or biomass, we need a biomass to electricity conversion system. A low-cost biomass to electric energy conversion husk powered system was imported from the Husk Power Systems of India. The system was installed in 2012 in Tiribogo Village, Muduma Parish in Mpigi District supplying 32kWe power to an isolated power grid. The system has operated since October 2012 with a daily usage of 7 hours. The biomass flow rate of 30 kg/hr for maize cobs and 25 kg/hr for coffee husks. The power output measured was 34 kW with line voltage of 244 V/ 50 Hz and phase voltage 422 V with a power factor of 0.85 at the generation side. The specific fuel consumption was 0.88 kg/kWh for maize cobs and 0.74 kg/kWh for coffee husks. The system electrical efficiency was 20.5% for maize cobs and 30.2% for coffee husk. The solid waste products generated were 12% for maize cobs and 10% for coffee husks of the total biomass fuel put into the gasifier. A software business model was generated using RETScreen software, considering the total cost of inputs and cost sales, the unit cost of power was found to be US$ 0.259 (UGX 686/=). The business simple payback was 3.3 years for maize cobs and 3.4 years for coffee husks. The break even period for the business was found to be 6.2 years for maize cobs and 6.3 years for coffee husks respectively if all power generated is sold. The fact that maize cobs were offered free from the community with transport cost of USD 15 per ton and coffee husk were bought at a rate of USD 40 inclusive transport per ton caused the difference in the financial parameters. In conclusion the operation of a 32 kWe power plant was found satisfactory using the local biomass and it produced more power than the community could consume or buy at that time therefore it is recommended for the rural communities generating 7 tons of annually.
Keywords: Rural electrification, isolated grid, Biomass, Husk power system